USING THE BLENDED LEARNING MODEL IN TEACHING FOREIGN LANGUAGES - Karabitskova , N. (Problems of Engineer-Pedagogical Education, 2023)
Peculiarities of the use of educational information technologies in foreign language teaching of students of non-speaking higher education institutions are studied. The educationalconcept of blended learning is proposed, which combines all the characteristics of informational educational technologies, and also reveals the possibilities of this type of learning as a means of increasing the effectiveness of the educational process. The mechanism for implementing the concept of blended learning as a process involves the creation of a comfortable educational information environment, a communication system that presents all the necessary educational information. Blended learning approaches have proven to be one of the most popular technologies today, because they allow you to take advantage of the flexibility and convenience of a distance course and the advantages of a traditional classroom. The growing popularity of blended learning in different countries of the world, including Ukraine, is caused not only by hopes for its high pedagogical effectiveness, but also by external economic factors. As expected, blended learning will reduce the cost of classroom, personnel, logistical and infrastructural support of the educational process, although to a lesser extent than distance learning. There is a methodological deficit associated with the lack of a generally accepted typology of blended learning organization models that has stable, didactically verified and at the same time simple and clear grounds, easy to understand andeasy to use not only for researchers, but also for practitioners. Foreign language teachers face a number of problems that require immediate solutions. In this regard, educational information technologies (EIT) are widely used in the educational process along with traditional teaching methods. There is an educational concept that combines all the characteristics of EIT, as the educational process uses distance learning, classroom classes, and learning via the Internet.